The Impact of Social Media on Knowledge Creation, Innovation, and Performance in Small and Medium Enterprises - Merry Mita Moy; Eko Ruddy Cahyadi; Elisa Anggraeni (School of Business, IPB University (SB-IPB), 2020)
In the globalization era, social media is widely used by small and medium enterprises (SMEs) to promote and market their products. However, there is still a limited objective of this study the effectiveness of social media in improving the business performance of SMEs. This study analyzes the effect of social media on knowledge creation, innovation, and performance in SMEs in Jabodetabek (Indonesia). This study combines online and offline methods to collect data from a sample of 384 SMEs. Data was analyzed SEM-PLS. The variables are social media, knowledge creation, innovation, and performance. The result is that social media does not havea direct impact on performance. However, social media has a significant influence on business performance, moderating knowledge creation, and innovation. Effectiveness of social media on improving business will the partner use for knowledge creation and innovation. Keywords: social media, knowledge creation, innovation, performance, SMEs